Identification and characterization of sources for photo‐ and thermo‐insensitivity in Vigna species. Issue 6 (13th October 2014) - Pratap, Aditya; Basu, Partha Sarathi; Gupta, Sanjeev; Malviya, Nupur; Rajan, Neha; Tomar, Rakhi; Madhavan, Latha; Nadarajan, Nagasamy; Singh, Narendra Pratap; Prasad, M.
Abstract Cultivation of the same varieties of mungbean and blackgram across different seasons and locations is constrained by their photo‐ and thermo‐sensitive behaviour. Developing insensitive genotypes, which can fit well across all seasons, requires robust donors which would provide genes imparting this trait. This study was undertaken to identify such donors in the Vigna species. Forty‐eight accessions belonging to 13 Vigna species and eight released cultivars were evaluated under natural field conditions. Among these, two accessions, viz. V. umbellata (IC251442) and V. glabrescens (IC251372) were found photo‐ and thermo‐insensitive as these were able to flower and set pods at temperatures as high as 43.9°C and as low as 2.7°C. Pollen viability studies indicated viable pollen (>75% at 2.7°C and >85% at 41.9°C) and normal pollen tube growth at both the extremes of temperature. The identified V. glabrescens accession has long, constricted pods and dark green, mottled seeds while V. umbellata has smooth, curved pods and shining, oval, large seeds. Both these accessions can be utilized in developing photo–thermo insensitive genotypes in cultivated Vigna species.